Structural development and brain asymmetry in the fronto-limbic regions in preschool-aged children - Lee, Gang Yi; Youn, Young-Ah; Jang, Yong Hun; Kim, Hyuna; Lee, Joo Young; Lee, Young Jun; Jung, Minyoung; Lee, Hyun Ju (Frontiers in Pediatrics, 2024)
Early-life experiences play a crucial role in the development of the fronto-limbic regions, influencing both macro-and microstructural changes in the brain. These alterations profoundly impact cognitive, social-emotional functions. Recently, early limbic structural alterations have been associated with numerous neurological and psychiatric morbidities. Although identifying normative developmental trajectories is essential for determining brain alterations, only a few studies have focused on examining the normative trajectories in the fronto-limbic regions during preschool-aged children. The aim of this study was to investigate the structural-developmental trajectory of the frontolimbic regions using the cortical thickness, volume, and subcortical volume in 57 healthy and typical preschool-aged children between 1 and 5 years and examined the early lateralization patterns during the development of the fronto-limbic regions. Regarding brain lateralization, remarkable asymmetry was detected in the volume of thalamus and the cortical regions excluding the lateral orbitofrontal cortex in the fronto-limbic regions. This study of preschool-aged children may fill the knowledge gaps regarding the developmental patterns and hemispheric asymmetries of the fronto-limbic regions between newborns and adolescents.